2014
DOI: 10.1177/1934578x1400900134
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant and Antimicrobial Activity of Essential Oil and Extracts of Tragopogon graminifolius, a Medicinal Herb from Iran

Abstract: Tragopogon graminifolius DC., family Compositae, is widely consumed as a green vegetable in the west of Iran and for the treatment of gastrointestinal and hepatic ailments. In this study, the chemical composition of the essential oil from T. graminifolius aerial parts was evaluated by gas chromatography and gas chromatography mass spectrometry. Moreover, antioxidant and antimicrobial activity of the essential oil and various extracts of T. graminifolius were determined. Fifty-eight compounds representing 87.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Farzaei et al. reported the presence of five phenolic compounds including p -coumaric acid, ferulic acid, catechin, gallic acid and caffeic acid in the hydroalcoholic extract of T. graminifolius aerial parts 11 . TG essential oil contains n -hexadecanoic acid, β -caryophyllene, heneicosane and nonanal as major components.…”
Section: Introductionmentioning
confidence: 99%
“…Farzaei et al. reported the presence of five phenolic compounds including p -coumaric acid, ferulic acid, catechin, gallic acid and caffeic acid in the hydroalcoholic extract of T. graminifolius aerial parts 11 . TG essential oil contains n -hexadecanoic acid, β -caryophyllene, heneicosane and nonanal as major components.…”
Section: Introductionmentioning
confidence: 99%
“…For example, palmitic acid was reported to be a more effective free radical scavenger than β-carotene [28]. n-Hexadecanoic acid may also contribute to the antioxidant activity [29].We have found that Phyllospora comosa (Crayweed), a species of brown algae in the Seirococcaceae family, has the highest level of polyphenols and also highest free radical scavenging activity. It also contains small amounts of fucoxanthin.…”
Section: Figmentioning
confidence: 95%
“…The phytoconstituents of MO extract were identified based on the NIST and Wiley mass spectral library. 24,25…”
Section: Gas Chromatography-mass Spectrometric Analysismentioning
confidence: 99%